Analisis Proksimat dan Nilai Kalor Biopelet Tandan Kosong Kelapa Sawit (TKKS) sebagai Sumber Energi Terbarukan - Eva Riana Br Bangun; Jufrizal Jufrizal; Nurdiana Nurdiana (CV. IRA PUBLISHING, 2025)
The palm oil industry in Indonesia generates a large amount of solid waste in the form of Empty Fruit Bunches (EFB). This waste is often underutilized and poses environmental challenges. The high lignocellulosic content of EFB offers significant potential for its development as a renewable biomass fuel. This study aims to evaluate the proximate composition and calorific value of EFB to assess its feasibility as a raw material for bio pellets. The experimental procedures included drying, shredding, grinding, and palletization, followed by laboratory testing based on SNI 8021:2014, SNI 7709:2019, and EN ISO 17225 standards. The results showed a moisture content of 7.85% and an ash content of 7.97%, both within acceptable limits, although the ash level was relatively high. Furthermore, EFB contained 24.20% carbohydrates and 37.99% crude fiber, which contributes to the structural stability of the bio pellets. The calorific value obtained was 1200 kcal/kg, which is considerably lower than values reported in previous studies (≥3500 kcal/kg). These findings highlight the potential of EFB as a renewable energy source while underscoring the need for process optimization to meet quality standards, with possible applications in small-scale and household energy generation.